Implementation of Quintuple Helix in the Development and Improvement of SMEs Competitiveness in Banyuwangi Regency - Herdiana Dyah Susanti; Dian Arief Pradana (Britain International for Academic Research (BIAR) Publisher, 2021)
Innovation is an interactive result that involves various types of actors based on the helix concept where each actor contributes according to its role. University, Industry, Government, Civil Society and media and culture-based society, society and natural environment in the concept of quintuple helix. This study aims to (1) Demonstrate the relationship between quintuple helix in developing SMEs competitiveness, (2) Effectiveness of the application of quintuple helix in developing SMEs competitiveness. This research is almost the same as experimental research with the pre-test - post-test results of the application of quintuple helix at SMEs in Banyuwangi Regency. The results of this study show the role of the University, Industry, Government, Civil Society as well as media and culture-based society, society and the natural environment in the concept of quintuple helix can improve the competitiveness of SMEs, enhance the capabilities of HR, improve the quality, and competitiveness of products produced by SMEs.